Behavior and design of FRP bonded autoclaved aerated concrete beams. (3rd May 2021) - Tuncer, Erturk; Binici, Baris; Canbay, Erdem
Highlights: CFRP/GFRP bonded and steel-reinforced AAC beams were investigated. Ductility, stiffness, strength, energy absorption capacity and cost were discussed. Test results were compared with section analyses and finite element simulations. ACI 440.2R overestimated debonding strain based on test and modeling results. FRP-reinforced specimens can provide satisfactory structural performance. Abstract: Fiber Reinforced Polymers (FRPs) have advantages such as lightness, high strength, and suppressing corrosion risk. There is a vast amount of research on the FRP strengthening of reinforced concrete elements. However, the behavior of FRP bonded Autoclaved Aerated Concrete (AAC) beams has not been extensively investigated in the past. In this study, several experiments were conducted to explore the performance of FRP bonded AAC beams. In this scope, unidirectional single layer carbon and glass fiber laminates with half or full of the beam width were bonded to the AAC. Test results were mainly evaluated by comparing the stiffness, strength, ductility, energy absorption capacity, and the cost of materials. Additionally, a numerical study (based on section analysis and finite element simulation) was conducted to estimate the load-deformation response of the specimens. Based on the analysis results, effective FRP strains were evaluated and compared with the recommendations given in the ACI 440.2R design guidelines for FRPs bonded to reinforced concrete. According to the limited test data, a 60% reduction appears to be appropriate while computing the effective FRP strains for FRP bonded AAC beams.